Reconstruction after Robotic Head and Neck Surgery: When and Why - Longfield, Evan A.; Holsinger, F. Christopher; Selber, Jesse C. (Journal of Reconstructive Microsurgery, 2012)
The advancement of robotically assisted surgery during the last decade has seen a revolution in the approach to surgical oncologic resection, moving toward reducing patient morbidity without compromising oncologic outcomes. In no field has this been more dramatic than in the application of transoral robotic surgery (TORS), using the da Vinci surgical system for resecting tumors of the head and neck. This organ-preserving technique allows the surgeon to remove tumors of the upper aerodigestive tract without external incisions and potentially spare the patient adjuvant treatment. The introduction of TORS improves upon current transoral techniques to the oropharynx and supraglottis. The traditional conception of TORS is that it would be used for smaller tumors and defects would be permitted to heal by secondary intention; however, as head and neck surgeons pursue larger tumors robotically, robotic-assisted reconstruction has entered the paradigm. Given the relative infancy of these procedures, clear guidelines for when reconstruction is warranted do not exist. The current literature, thus far, has focused on feasibility, safety, and implement of the robot in reconstruction. We reviewed the current literature pertinent to TORS reconstruction focusing on patient selection, tumor size, and location. Furthermore, we briefly review our own experience of 20 TORS procedures involving robotic-assisted reconstructions. Finally, we provide an algorithmic approach to determining the need for reconstruction in a given patient. This focuses on four key criteria: tumor location, tumor extent, prior treatment, and patient-specific factors.
Keywords: robotic reconstruction; da Vinci; tors